Intra-wave-phase cross-shore profile modelling by using boundary-fitted slowly moving grid - Hyoseob Kim (Mathematical Models in Engineering, 2016)
Coastal bed profile change is described by bed load, pick-up, and settling on a boundary-fitted moving grid. Existing bed load formula is modified by changing threshold bed shear stress to reflect local bed slope. A numerical model system adopting the above function is developed to simulate cross-shore sediment transport around swash zone with steep bed slope as well as surf zone. The model system adopts a moving boundary grid which fits bed boundary slope, and other horizontal grid lines are parallel to the bed grid line. The model system is composed of flow module and sediment transport module. The flow module solves continuity equation and Reynolds-average Navier-Stokes momentum equations in intra-wave-phase manner. The flow module provides detailed flow information including near-bed fluid velocity which varies asymmetrically within a regular wave period near sea-bed and wave-phase average undertow profile of main fluid body including wave boundary layer. The sediment transport module solves sediment mass conservation equation. Exchange of sediment mass between bed itself and fluid column containing suspended sediment happens through pick-up and deposition. Wild bed level undulation is controlled by using a smoothing method. Model system is applied to two extreme cases of sand experiments by Kajima et al., and reasonable agreements between measurements and computations are obtained for both onshore-dominant and offshore-dominant cases.